2007
DOI: 10.1017/s0022215107008353
|View full text |Cite
|
Sign up to set email alerts
|

Buccinator myomucosal flap: clinical results and review of anatomy, surgical technique and applications

Abstract: The buccinator myomycosal flap is a dependable flap with good functional outcome and low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 15 publications
1
25
0
3
Order By: Relevance
“…Variations of a buccinator flap based on the facial artery10, 11, 15, 17–20 have been described by multiple authors and will not be elucidated upon. The basis of the FAB flap most closely resembles the buccinator myomucosal reverse flow island flap reported in 1999 by Zhao et al10 Similarly, Fan et al21 described the use of reversed buccinator musculomucosal flaps for reconstruction of defects resulting from resection of nasal inverted papillomas.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of a buccinator flap based on the facial artery10, 11, 15, 17–20 have been described by multiple authors and will not be elucidated upon. The basis of the FAB flap most closely resembles the buccinator myomucosal reverse flow island flap reported in 1999 by Zhao et al10 Similarly, Fan et al21 described the use of reversed buccinator musculomucosal flaps for reconstruction of defects resulting from resection of nasal inverted papillomas.…”
Section: Discussionmentioning
confidence: 99%
“…The various cheek flaps have shown great applicability with only minor complications, in particular in the covering of medium‐sized substance loss in the floor of the mouth or exposure of the mandible. Hinged posteriorly and thus based on the buccal artery or random flow, the flap may cover defects in the anterior oropharynx (tonsillar fossa, base of tongue, and soft palate) …”
Section: Introductionmentioning
confidence: 99%
“…The mouth opening improved after mouth opening exercises. Van Lierop et al 22 reported no trismus in his 14 patients, while Seung Hoon Woo et al 21 reported trismus in one of his 11 patients who had a buccal flap.…”
Section: Discussionmentioning
confidence: 94%